2016
DOI: 10.1111/jnc.13888
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways for elevating extracellular adenosine in the rat hippocampal CA1 region characterized by adenosine sensor cells

Abstract: Extracellular adenosine in the brain, which modulates various physiological and pathological processes, fluctuates in a complicated manner that reflects the circadian cycle, neuronal activity, metabolism and disease states. The dynamics of extracellular adenosine in the brain are not fully understood, largely because of the lack of simple and reliable methods of measuring time-dependent changes in tissue adenosine distribution. This study describes the development of a biosensor, designated an adenosine sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
(92 reference statements)
2
12
0
Order By: Relevance
“…Extracellular adenosine synthesis begins with the phospho-ester hydrolysis of its precursor molecule ADP or ATP, which is released by tissues (e.g., brain) (Bekar et al, 2008), electrically stimulated sensor cells (Yamashiro et al, 2017), extracellular vesicles, platelet vesicles (Weissmüller et al, 2008) and platelets in the blood (Kohli et al, 2016). ATP is rapidly converted to ADP and AMP via the enzyme ecto-nucleoside triphosphate diphosphohydrolase 1 (CD39) (Grenz et al, 2007;Köhler et al, 2007) and is further metabolized to form adenosine via ecto-5-nucleotidase (CD73) (Fredholm et al, 2007).…”
Section: Adenosine Synthesismentioning
confidence: 99%
“…Extracellular adenosine synthesis begins with the phospho-ester hydrolysis of its precursor molecule ADP or ATP, which is released by tissues (e.g., brain) (Bekar et al, 2008), electrically stimulated sensor cells (Yamashiro et al, 2017), extracellular vesicles, platelet vesicles (Weissmüller et al, 2008) and platelets in the blood (Kohli et al, 2016). ATP is rapidly converted to ADP and AMP via the enzyme ecto-nucleoside triphosphate diphosphohydrolase 1 (CD39) (Grenz et al, 2007;Köhler et al, 2007) and is further metabolized to form adenosine via ecto-5-nucleotidase (CD73) (Fredholm et al, 2007).…”
Section: Adenosine Synthesismentioning
confidence: 99%
“…The subsequent decay of OR EPSPs to control level within minutes likely reflects restoration of tonic inhibition once A 2A Rs desensitize 67 . By contrast, A 2A R desensitization could be weaker during OR pairing than during RAD pairing, since electrical stimulation in stratum oriens elevates extracellular adenosine less than electrical stimulation in stratum radiatum 68 . Interestingly, adenosine release during OR stimulation involves L-type voltage-gated Ca 2+ channels and/or Ca 2+ -induced Ca 2+ release 68 , and could explain why a blocker of L-type voltage-gated Ca 2+ channels reduced OR pairing induced LTP.…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, A 2A R desensitization could be weaker during OR pairing than during RAD pairing, since electrical stimulation in stratum oriens elevates extracellular adenosine less than electrical stimulation in stratum radiatum 68 . Interestingly, adenosine release during OR stimulation involves L-type voltage-gated Ca 2+ channels and/or Ca 2+ -induced Ca 2+ release 68 , and could explain why a blocker of L-type voltage-gated Ca 2+ channels reduced OR pairing induced LTP. Thus, distinct pathways appear capable to elevate extracellular adenosine in CA1 (NMDA in RAD and ‘Ca 2+ ’ in OR) and could be involved in the timing-dependent, asymmetric plasticity in CA1.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have revealed that both L-type calcium channels and calcium-induced calcium release can induce post-synaptic adenosine elevation [ 117 ] and that calcium signaling acts upon Per1 / 2 genes directly via CREB in mammalian cells [ 103 , 115 , 118 ]. In addition, A 1 R can also inhibit L-type calcium channels via its G i [ 3 ].…”
Section: Adenosine a 1 R And A 2a ...mentioning
confidence: 99%